Communication-related quality of life in adults with acquired neurological disorders who use augmentative and alternative communication: a scoping review of existing tools - Grigoriou, Stavroulla; LaValley, Mimi; Kola, Erasmia; Koul, Rajinder; Pampoulou, Eliada (My University, 2025)
Augmentative and alternative communication (AAC) has potential to significantly enhance the QoL for those with severe communication impairment as a consequence of acquired neurological disorders. Whilst there has been a progress in the research on AAC for individuals with acquired neurological disorders and effects on QoL, there are still unanswered questions that need further investigation, specifically in the area of communication-related quality of life (CRQoL). The purpose of this scoping review is to explore tools to evaluate CRQoL in adults with acquired neurological disorders who use AAC. It examines areas of communication these tools are focused on and methods of access for individuals with acquired communication disorders who might also experience physical, cognitive, and linguistic impairment. Six databases were searched with predetermined search terms. Results indicated that 10 papers used assessment tools related to CRQoL. Gaps in the research included limited data on how communication partners were involved in assessment. Overall, findings indicate a lack of information about how AAC users can access assessment tools with adaptations or communication partner support. Future research should focus on CRQoL tools and access methods for AAC users.
Keywords: Quality of life; acquired neurological disorders; augmentative and alternative communication; communication; scoping review